Climatically determined spatial and temporal changes in the biomass of Pinus sp. of Eurasia in the context of the law of the limiting factor - Usoltsev, Vladimir Andreevich; Zukow, Walery; Tsepordey, Ivan Stepanovich (Ecological Questions, 2022)
Forest ecosystems play an essential role in climate stabilization, and the study of influence of climate change on their biomass and carbon depositing is of paramount importance. The objective of this study was (a) to verify the operation of the law of the limiting factor at the transcontinental level when modeling changes in the biomass of trees and stands of the two-needled subgenus Pinus sp. of Eurasia in relation to geographically determined indicators of temperatures and precipitation, and (b) to show the possibility of using the constructed climate-conditioned models of tree and stand biomass in predicting temporal changes in tree and stand biomass based on the principle of space-for-time substitution. As a result of the implementation of the principles of the limiting factor and space-for-time substitution, a common pattern has been established on tree and stand levels: in sufficiently moisture–rich climatic zones, an increase in temperature by 1°C with a constant amount of precipitation causes an increase in aboveground biomass, and in moisture–deficient zones - its decrease; in warm climatic zones, a decrease in precipitation by 100 mm at a constant average January temperature causes a decrease in aboveground biomass, and in cold climatic zones - its increase.